Pengaruh Pelaksanaan E-Filing, E-Billing, Kesadaran Wajib Pajak, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Pribadi di Kantor Pelayanan Pajak Utama Medan Belawan - Nabila, Devi; Lubis, Nurul Izzah (ProBisnis : Jurnal Manajemen, 2025)
Compliance of individual taxpayers refers to their attitudes and behaviors in carrying out tax obligations in accordance with prevailing laws and regulations. This study aims to analyze the influence of E-Filing, E-Billing, taxpayer awareness, and tax sanctions on the compliance of individual taxpayers at the Pratama Tax Office (KPP) Medan Belawan. The population in this research includes all individual taxpayers registered at KPP Pratama Medan Belawan, totaling 214,866 taxpayers, with a research sample of 100 respondents. The study applies a quantitative approach, where each variable is measured using a Likert scale. Primary data were obtained through the distribution of questionnaires and analyzed using several statistical tests, including data quality tests (validity and reliability), classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (Adjusted R²). The findings indicate that E-Filing and E-Billing do not have a significant influence on individual taxpayer compliance, whereas taxpayer awareness and tax sanctions have a positive and significant impact. Collectively, these four variables show a significant effect on the compliance of individual taxpayers at KPP Pratama Medan Belawan.